Réponses

  • Utilisateur Brainly
2013-06-13T18:12:50+02:00

1) a) fonction définie par l'expression :

f(x)=((x+3)x-1)x+2

     =(x²+3x-1)x+2

     =x³+3x²-x+2

 

b) on utilise les touches :

- Tbl Set

- Table

- Fix 1

 

c) f(3,7) ≈ 90,0 et f(-1,2) ≈ 5,8

étapes du calcul :

x=3,7

x+3=6,7

(x+3)x=24,79

(x+3)x-1=23,79

((x+3)x-1)x=88,023

((x+3)x-1)x+2=90,023

 

x=-1,2

x+3=1,8

(x+3)x=-2,16

(x+3)x-1=-3,16

((x+3)x-1)x=3,792

((x+3)x-1)x+2=5,792

 

2) fonction f développée et réduite :

f(x)=((x+3)x-1)x+2

     =(x²+3x-1)x+2

     =x³+3x²-x+2